Proteomická analýza solubilních proteinů důležitých u dětské leukémie - Hrušák, Ondřej; Weiser, Jaroslav (Iga MZ ČR, 2010)
ALL is the most frequent malignant disease of childhood. Surviving of leukemic cells is dependent on the bone marrow microenvironment, therefore we will focus on the analysis of soluble proteins pattern in the bone marrow plasma of children with ALL. Soluble proteins pattern will be analyzed by proteomic methods. Proteins differently expressed in ALL and control bone marrow plasma will be verified by flow cytometry and enzyme-linked immunoanalysis investigation. Identified proteins can be used as diagnostic markers of leukemias with worse prognosis or as the potential therapeutic targets, if these proteins significantly support the surviving of leukemic cells.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: výsledek terapie; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Acute Disease; Proteomics; Prognosis; Child; akutní nemoc; proteomika; Treatment Outcome; hematologie a transfuzní lékařství; prognóza; dítě; krevní plazma; onkologie; pediatrie; Plasma; akutní lymfatická leukemie